The Effectiveness of Sodium Hydroxide Precipitation in Impurity Removal during NaCl Recovery from Bittern Waste Water - Indah Maharani Puspitasari; Andreansyah Brilliant Putra; Caecilia Pujiastuti; Renova Panjaitan (G-Tech: Jurnal Teknologi Terapan, 2025)
Recovery of sodium chloride (NaCl) from bittern, a by-product of salt production, is often hindered by impurities such as Mg²⁺ and Ca²⁺, which reduce NaCl purity. This study evaluated the effect of sodium hydroxide (NaOH) concentration and stirring time on NaCl recovery, using NaOH concentrations of 4.6 until 8.02 N and stirring durations of 20 until 60 minutes at a constant stirring speed of 300 rpm. The process involved NaOH addition, stirring, filtration of precipitates, and NaCl crystallization. Parameters such as impurity levels, pH, NaCl purity, and recovery percentage were analyzed. Results indicated that higher NaOH concentrations and longer stirring times generally decreased impurity levels and improved NaCl recovery. Optimal conditions 5.8 N NaOH and 50 minutes stirring yielded an impurity level of 0.0359%, NaCl purity of 89.61%, and a recovery rate of 85.57%. This study presents a novel approach by optimizing NaOH concentration and stirring time parameters to effectively minimize divalent ion contamination, thereby enhancing NaCl recovery from bittern. The findings have direct applicability in improving the efficiency of salt recovery processes in coastal salt industries, contributing to more sustainable salt production systems.